A Different Approach: Effect of Mechanical Alloying on Pack Boronizing - Albayrak, Muhammet Gokhan; Evin, Ertan (Springer, 2024)
Surface coating processes are carried out at high temperatures, so high heat input is applied to the material to be coated and may cause internal structure deterioration. In order to overcome this situation, the ability to reduce the coating temperature with a pretreatment such as Mechanical Activation was investigated in this study. In order to minimize the effect of alloying elements, DIN St28 steel is used. Powders containing B+SiC+KBF4 were mechanically alloyed by planetary ball milling devices to 10 and 20 h, respectively. By mixing boron-containing powder and sodium silicate, the samples were boronized at 923-1173 K temperature and 3-12 h. At the end of the mechanical alloying process, it was determined that the powder particle sizes were in the nanometer scale. According to the microstructure analysis, a single-layer Fe2B structure was successfully obtained on the samples surfaces. While no boride layers were formed on the sample surfaces at temperatures below 1023 K without MA pretreatment, boride layers were formed under these temperatures with MA pre-treatment. It has been observed that the depth of the Fe2B boride layer, which has achieved high diffusivity by creating many defects in the form of nanometer-sized crystal particles, increased with repeated fracture and cold welding of the powder particles with increasing mechanical alloying times. By calculating the activation energies of the powders, their relations with the mechanically unalloyed samples were compared and empirical formulas that could be used for similar experimental conditions were produced. The highest microhardness value was measured as 2200 HV and above.
Keywords: boronizing; diffusion; mechanical alloying